2002
DOI: 10.1193/1.1516201
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Building Loss Estimates to Major Uncertain Variables

Abstract: This paper examines the question of which sources of uncertainty most strongly affect the repair cost of a building in a future earthquake. Uncertainties examined here include spectral acceleration, ground-motion details, mass, damping, structural force-deformation behavior, building-component fragility, contractor costs, and the contractor's overhead and profit. We measure the variation (or swing) of the repair cost when each basic input variable except one is taken at its median value, and the remaining vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(165 citation statements)
references
References 11 publications
6
159
0
Order By: Relevance
“…In order to introduce the PDF of ratio of equivalent viscous damping ( ), here the work of Porter et al [34] is used, in which the authors have compiled the results of some researches aimed at estimation of ξ for different kinds of structures. Porter et al concluded that a reasonable value for coefficient of variation (C.O.V) for this parameter should be between 0.3 and 0.4.…”
Section: Parameters Of the Structural Modelmentioning
confidence: 99%
“…In order to introduce the PDF of ratio of equivalent viscous damping ( ), here the work of Porter et al [34] is used, in which the authors have compiled the results of some researches aimed at estimation of ξ for different kinds of structures. Porter et al concluded that a reasonable value for coefficient of variation (C.O.V) for this parameter should be between 0.3 and 0.4.…”
Section: Parameters Of the Structural Modelmentioning
confidence: 99%
“…They added the capability of resolving contradictions between experts' opinions. The sensitivity of seismic loss estimation methods to input variables and criteria was investigated by (Porter, Beck, & Shaikhutdinov, 2002). Aghamohammadi et al (2013) assessed the human seismic vulnerability of urban areas which is the estimation of number of humans may die in an earthquake.…”
Section: Related Workmentioning
confidence: 99%
“…ABV has proven to be a useful research tool. We have used it to evaluate seismic risk and to perform benefit-cost analysis of seismic-risk mitigation for steel-frame, woodframe, and concrete buildings, and to explore major contributors to the uncertainty in economic seismic risk (Beck et al 1999, Porter et al 2002b, Beck et al 2002, Porter et al 2002a). …”
Section: Assembly-based Vulnerabilitymentioning
confidence: 99%